Forensics, Elasticities and Benford's Law - Banu Demir Pakel; Beata Smarzynska Javorcik (Center for Economic Studies and ifo Institute (CESifo), 2018)
Estimates of the trade elasticity based on actual trade policy changes are scarce, and the few that exist are all over the place. This paper offers a setting where an exogenous increase in a border tax can be used to estimate the trade elasticity. It shows theoretically and empirically that if evasion of border taxes is not taken into account, the trade elasticity is estimated with a large downward bias, leading to miscalculation of gains from trade. The paper also contributes to the literature by proposing two new methods of detecting evasion of border taxes.
Keywords: F10; 330; trade elasticity; tax evasion; trade financing; border taxes; Benford's law